HUBUNGAN GRIT DENGAN ORGANIZATIONAL CITIZENSHIP BEHAVIOR PADA KARYAWAN DI UNIVERSITAS X - Shanty Sudarjy; Vania Priskila (Universitas Trunojoyo Madura, 2019)
Grit is defined as perseverance of effort and consistency of interest. This is to be seen by researchers in relation to organizational citizenship behavior in the scope of work of employees at X University. This study aims to understand the relationship between Grit and OCB for employee at X University. The method in this study using correlational research. The population in this study were 295 people with a sample of 110 people. The research instrument used in this study was adapted from the Grit measuring instrument developed by Angela Lee Duckworth (2007) and for organizational citizenship behavior using Williams and Anderson (1991) measurement tools that distinguish OCB into two, namely OCB-Organization (OCB-O) and OCB Individual (OCB-I). The results of this study show the positive correlation between Grit and OCB-I (r = 0.270, α = 0.04) but do not correlate with OCB-O (r = 0.04, α = 0.055).